Planktic Foraminifera Extinctions and Delayed Biotic Recovery in the Late Maastrichtian-Early Danian: Link to Global Environmental Catastrophes? - Punekar, Jahnavi (Princeton, NJ : Princeton University, 2016)
The final ~3 myr of the Maastrichtian (Late Cretaceous) and the first ~2 myr of the Danian (Early Paleogene) showcase multiple climate shifts, major sea level fluctuations and significant faunal turnovers that are unique in geologic history. This interval (69.0-64.0 Ma) brackets the controversial Cretaceous-Tertiary boundary (KTB or K-Pg) mass extinction and two prominent global catastrophes: the Chicxulub impact and Deccan volcanism. The immediate cause for the KTB mass extinction, whether impact or volcanism, has remained controversial for the past 35 years. The main objective of this thesis is to bring some clarity to this controversial mass extinction, and to understand and isolate the contributions of each event to the long-term evolution, diversification and extinction trends recorded by planktic foraminiferal assemblages. In the past decade, three major phases of Deccan volcanism have been identified based on 40Ar/39Ar and magnetostratigraphy: phase-1 spanning the paleomagnetic chron C30r/C30n boundary (planktic foraminiferal zone CF4), phase-2 in the latest Maastrichtian C29r (zones CF1–CF2), and phase-3 in the early Danian C29n (P1b). Our results show that planktic foraminifera assemblages from the palaeo-Tethyean Egypt and Sinai record high- stress assemblages dominated by opportunist species Guembelitria tentatively coeval with each of the three volcanic phases. Guembelitria acme events correlative with phase-1 volcanism are relatively minor (<45%); maximum Guembelitria blooms (>80% of the total assemblage) are observed in CF1 spanning the last ~100 kyr of the Cretaceous, also correlative with abrupt climate warming and phase-2 Deccan volcanism. High-stress (50– 75% Guembelitria) is also observed in zone P1b, marked by another climate warming (Dan- C2 event) and a major negative carbon isotope excursion correlative with phase-3 volcanism. Our review of the entire KTB database (~300 sites worldwide) in context of the latest available dates for Deccan volcanism confirmed time-correlation of faunal high-stress events with the last two major phases of Deccan volcanism worldwide. The major phase-2 is invariably associated with blooms of the opportunist Guembelitriain shallow-marine assemblages from India through the Tethys to the Atlantic Ocean. Similar high-stress environments dominated by opportunist blooms are observed globally correlative with phase- 3 volcanism in the Danian zone P1b. Biotic recovery is observed in Danian zone P1c, only after phase-3 volcanism ended. Deccan volcanism can therefore account for the end- Maastrichtian high-stress that ended in the mass extinction, and the ~500 kyr delay in marine recovery, respectively. The cumulative loading of 10’s of thousands of Gigatons (Gt) of volcanogenic CO2 into the end-Cretaceous atmosphere within 10’s of thousand years would increase the atmospheric pCO2 on timescales that are recorded in the sediments. The potential acidification of oceans could have critically contributed to high environmental stress for marine calcifying organisms. Our study of the pre-KTB sediments from Bidart and Gamsbach show a concurrence of low magnetic susceptibility and high foraminifera test fragmentation index (FI), collectively forming the first-ever definitive evidence for ocean acidification linked to Deccan volcanism. We propose this carbonate crisis as a potentially lethal kill-mechanism for end-Cretaceous planktic foraminifera. The least studied of Deccan volcanic phases (phase-1) spans from upper C31n to middle C30n. Preliminary results from zone CF4 at DSDP Site 525A show a rapid warming (~2°C deep ocean) at base CF4 (upper C31n) associated with enhanced planktic fragmentation index (FI) indicative of lower surface ocean pH. A subsequent cooling (~1 °C surface ocean) is associated with a significant diversity decline, particularly for Archeoglobigerina cretacea, Globotruncana bulloides, G. gandolfi nsp., Contusotruncana fornicata, C. plummerae, and C. plicata. Increased environmental stress (onset C31n/C30r) continued in upper zone CF4 (C30n), supported by the appearance of Guembelitria cretacea in open marine settings. This stress event can be traced through the Tethys (Egypt, Israel) to the Indian Ocean (DSDP Site 217 and the Cauvery basin, SE India), and can be linked to two potentially coeval volcanic events – Ninetyeast Ridge volcanism and the onset of Deccan Trap volcanism. Absolute ages (U-Pb) of these volcanic events are vital to confirm the association.